Shoe-la-la! - Beaumont, Karen; Pham, LeUyen (New York : Scholastic Press, 2011)
Four girls go in search of the perfect pair of party shoes.
Publisher's Weekly, November 2010
Kirkus Review, December 2010
1.9
K-3
Keywords: Shoes -- Juvenile fiction; Stories in rhyme; Shoes -- Fiction; Stories in rhyme; Shoes -- Fiction; Picture books for children